Moral Values Representation in The ELT Textbook For Junior High School Students in Indonesia - Natasha Putri Setyo Wahyudi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examined how moral values are shown in the English for Nusantara textbook, which seventh-grade students in Indonesia use. The research followed a qualitative approach and used Critical Discourse Analysis (CDA) to understand how the visuals in the textbook represent moral values related to the Pancasila Student Profile. The Pancasila Student Profile highlights six central values: faith, global diversity, independence, cooperation, critical thinking, and creativity. I reviewed all the textbook visuals, including pictures, texts, and comic strips across the chapters. There were 84 visual artifacts in total. However, for this analysis, I only selected eight visuals. This was to focus on images that clearly showed the core moral values from the Pancasila Student Profile. I chose these eight images because they stood out in how well they represented the values and helped keep the analysis focused. This made the study manageable and ensured I did not repeat similar images. The analysis was based on Fairclough's three-dimensional framework, which looks at the text through description, interpretation, and explanation. The results showed that the most common moral values in the visuals were cooperation, global diversity, and faith. For example, the pictures of students working together, families praying, and showing cultural diversity were prominent. However, critical thinking and creativity were not as often shown. Only a few images encouraged students to think critically or creatively. In conclusion, the textbook does a good job teaching values like cooperation, respect for global diversity, and religious devotion, but it could do more to encourage critical thinking and creativity.
Reupload file repository 6 April 2026_Ratna
Keywords: Moral Values Representation; the ELT Textbook